Rights issue in the implementation of youth employment in Ukraine - Вишновецький, В. М.; Поліщук, Л. І. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article analyzed the problems of youth labor market and employment of young people in today anddefined ways to improve level of employment for young people in the labor market in Ukraine.